Ceramic core surface modification method for improving the inner cavity quality of single crystal hollow blades
Through the three surface modification treatment and firing technology of single crystal hollow blade ceramic core, the low melting point element volatility and recrystallization of ceramic core in high-temperature casting is solved, and the quality of the blade cavity and the strength of the ceramic core are improved. , achieving high temperature stability and mechanical performance improvement of the blade cavity.
Patent Information
- Application Number
- CN202411535101.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-10-31
AI Technical Summary
During the high-temperature casting of single crystal hollow blade castings, the low melting point elements of the silicon-based ceramic core are prone to evaporate, resulting in excess metal casting tumors and recrystallization in the inner cavity of the blade. The prior art is difficult to effectively solve these problems.
By using the three-step surface modification treatment method, the ceramic core blank is cleaned in alcohol, vacuumed, and immersed in the surface modified slurry for modification treatment, forming a protective layer to inhibit the volatility of low melting point elements. Then, the surface modified ceramic core with high temperature three-point bending strength was prepared.
Effectively inhibit the volatility of low melting point elements in the ceramic core, avoid unnecessary metal casting and recrystallization in the blade cavity, improve the quality of the blade cavity, ensure the strength and concession of the ceramic core, and avoid bending. Deformation and core leakage.
Smart Images

Figure CN119035461B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic core preparation in single crystal hollow blade precision casting, and in particular relates to a ceramic core surface modification method for improving the inner cavity quality of a single crystal hollow blade. Background Art
[0002] As the temperature of the front inlet of aircraft engines continues to increase, the inner cavity structure of hollow turbine blades is becoming more and more complex to improve the cooling effect of the blade cavity. In the process of gradual iteration and development of the blade cavity structure, silicon-based ceramic cores are widely used due to their low sintering temperature and easy removal, but the quality problem of the blade cavity during the casting process is becoming increasingly prominent.
[0003] First, when the single crystal hollow blade casting undergoes the process of melting, pouring or heat treatment, the low-melting-point elements of the silicon-based ceramic core are easily volatilized to form defects during the melting and pouring process. Therefore, the high-temperature alloy erodes the ceramic core during the pouring process, resulting in excess metal casting nodules in the inner cavity of the blade. In addition, the silicon-based ceramic core must have a certain strength to resist the mechanical and thermal shock of the molten metal, and a certain degree of yielding to avoid stress concentration in the inner cavity of the blade and cause recrystallization in the inner cavity.
[0004] At present, the industry mainly improves the stability of ceramic cores by adjusting the components of ceramic cores or coating the outer surface of ceramic cores. If the components of ceramic cores are adjusted, the size and performance of ceramic cores will change. If coating is applied, the coating will easily separate from the substrate layer during the casting process, resulting in poor bonding ability. Therefore, it is urgent to develop a ceramic core surface modification method for improving the quality of the inner cavity of single crystal hollow blades, so as to solve the problem of excess metal nodules and recrystallization in the inner cavity of blades during high-temperature casting.
[0005] The invention patent with application publication number CN118791291A discloses a high-performance silicon-based ceramic core and a preparation method for achieving a balance between solid content and viscosity. The mass percentage of each substance in the silicon-based ceramic core is 80-90wt% of composite ceramic powder and 10-20wt% of photosensitive resin; the mass percentage of each substance in the composite ceramic powder is 80-90wt% of matrix skeleton material and 10-20wt% of performance enhancer; the mass percentage of each substance in the matrix skeleton material is 80-90wt% of fused quartz and 5-10wt% of cristobalite. %, 5-10wt% silicon dioxide, the mass percentage of each substance in the performance enhancer is 70-85wt% silicon carbide, 5-15wt% zirconium carbide, and 10-15wt% boron carbide; the mass percentage of each substance in the photosensitive resin is 80-90wt% curing cross-linking agent, 5-10wt% viscosity auxiliary agent, 0.5-5wt% surface modifier, and 0.5-5wt% light curing auxiliary agent; the mass percentage of each substance in the surface modifier is 75-85wt% silane coupling agent and 15-25wt% polyether modified polydimethylsiloxane. This technical solution directly adds the surface modifier when preparing the ceramic core slurry, and then uses the prepared ceramic core slurry to prepare the ceramic core, and does not coat the surface modifier on the prepared ceramic core blank or the outer surface of the ceramic core, so this technical solution cannot solve the problem of metal casting nodules and recrystallization in the inner cavity of the blade during high-temperature casting. Summary of the invention
[0006] In order to solve the problems existing in the prior art, the present invention provides a ceramic core surface modification method for improving the inner cavity quality of a single crystal hollow blade, the modification method comprising the following steps in chronological order:
[0007] Step 1: manufacturing a ceramic core mold according to the designed ceramic core structure, and injecting the ceramic core slurry into the ceramic core mold by an injection molding machine for filling and pressing to obtain a ceramic core blank;
[0008] Step 2: Prepare surface modification slurry according to design requirements;
[0009] Step 3: Put the ceramic core blank into alcohol for cleaning, so that the surface of the ceramic core blank is clean and free of foreign matter; after the cleaning is completed, dry the ceramic core blank;
[0010] Step 4: After the drying process is completed, the ceramic core blank is placed in a vacuum device for vacuum treatment; after the vacuum treatment is completed, the ceramic core blank is completely immersed in the surface modification slurry for the first surface modification treatment;
[0011] Step 5: After the first surface modification treatment is completed, the ceramic core blank is directly immersed in the surface modification slurry for a second surface modification treatment without vacuum treatment;
[0012] Step 6: After the second surface modification treatment is completed, the ceramic core blank is directly immersed in the surface modification slurry for the third surface modification treatment without vacuum treatment;
[0013] Step 7: After the third surface modification treatment is completed, the ceramic core blank is placed in alcohol for cleaning and drying;
[0014] Step 8: Check the ceramic core blank and confirm that there are no obvious defects in its appearance, then insert the ceramic core blank into a calcined bowl filled with kaolin filler, and make the kaolin filler completely cover the ceramic core blank;
[0015] Step nine: placing the calcined pot containing the kaolin filler and the ceramic core blank into a calcining furnace for calcining. After the calcination is completed, a surface-modified ceramic core for improving the inner cavity quality of a single-crystal hollow blade is obtained.
[0016] Preferably, in step one, the mass percentage of each substance in the ceramic core slurry is 70-85wt% of ceramic powder and 15-30wt% of plasticizer; the mass percentage of each substance in the ceramic powder is 70-90wt% of quartz glass powder, 5-20wt% of zirconium silicate powder, and 5-10wt% of mullite whisker, and the median particle size of the quartz glass powder and the zirconium silicate powder are both 25-50μm; the mass percentage of each substance in the plasticizer is 80-85wt% of paraffin, 10-15wt% of beeswax, and 5-8wt% of polyethylene glycol.
[0017] The preparation process of the ceramic core slurry is as follows: first, quartz glass powder, zirconium silicate powder and mullite whisker are uniformly mixed at room temperature according to the designed material ratio to obtain ceramic powder; then, paraffin, beeswax and polyethylene glycol are placed in a container and heated to melt according to the designed material ratio, the heating temperature is 90-120° C., and the three substances are uniformly mixed to obtain a plasticizer; finally, the heating temperature is kept unchanged, the ceramic powder is added to the plasticizer and mixed uniformly to obtain the ceramic core slurry, and then the temperature is reduced to 80-100° C. and kept warm for standby use.
[0018] The pressing parameters of the ceramic core blank are injection temperature of 80-100° C., injection pressure of 4-6 MPa, and holding time of 5-35 s.
[0019] In any of the above schemes, it is preferred that in step 2, the mass percentage of each substance in the surface modified slurry is 50-65wt% of alumina powder, 30-45wt% of aluminum sol, 1-5wt% of silica sol, and 0.5-1wt% of dispersant; the median particle size of the alumina powder is 1-10μm, and the median particle sizes of the aluminum sol and the silica sol are both 5-30nm; the mass percentage of each substance in the dispersant is 30-50wt% of carboxymethyl cellulose emulsifier and 50-70wt% of polyoxyethylene.
[0020] In any of the above schemes, it is preferred that in step 2, the preparation process of the surface modified slurry is as follows: first, according to the designed material ratio, the carboxymethyl cellulose emulsifier and the polyethylene oxide are electromagnetically stirred at room temperature at a stirring speed of 50-100rpm and a stirring time of 0.5-1h to ensure that the two substances are evenly mixed to obtain a dispersant; then, according to the designed material ratio, the aluminum sol and the silica sol are electromagnetically stirred at room temperature at a stirring speed of 50-100rpm and a stirring time of 10-30min to ensure that the two substances are evenly mixed; finally, alumina powder and a dispersant are added to the mixture of aluminum sol and silica sol, and electromagnetically stirred at room temperature at a stirring speed of 100-200rpm and a stirring time of 1-3h to ensure that the substances are evenly mixed to obtain a surface modified slurry.
[0021] In any of the above schemes, it is preferred that in step three, the drying treatment parameters of the ceramic core blank are: ambient temperature 23±5°C, ambient humidity 50±5%, wind speed 0.5-2m / s, drying time 0.5-3h, and the moisture content of the ceramic core blank after drying is below 2.5%.
[0022] In any of the above schemes, it is preferred that in step four, the ceramic core blank is placed in a vacuum pumping device for vacuum treatment, and the vacuum degree is drawn to -0.05~-0.08MPa; the first surface modification process of the ceramic core blank is to completely immerse the vacuumized ceramic core blank in the surface modification slurry for dipping, and the dipping time is 0.5-3h; after the dipping is completed, the ceramic core blank is taken out for slurry control, and the slurry control time is 10-15s; after the slurry control is completed, the ceramic core blank is dried, the ambient temperature is 23±5℃, the ambient humidity is 50±5%, the wind speed is 0.5-2m / s, and the drying time is 0.5-3h.
[0023] In any of the above schemes, it is preferred that in step five, the second surface modification process of the ceramic core blank is to completely immerse the ceramic core blank after the first surface modification treatment in the surface modification slurry for dipping, and the dipping time is 0.5-1h; after the dipping is completed, the ceramic core blank is taken out for slurry control, and the slurry control time is 5-8s; after the slurry control is completed, the ceramic core blank is dried, the ambient temperature is 23±5℃, the ambient humidity is 50±5%, the wind speed is 0.5-2m / s, and the drying time is 0.5-3h.
[0024] In any of the above schemes, it is preferred that in step six, the third surface modification process of the ceramic core blank is to completely immerse the ceramic core blank after the second surface modification treatment in the surface modification slurry for dipping, and the dipping time is 0.5-1h; after the dipping is completed, the ceramic core blank is taken out for slurry control, and the slurry control time is 3-5s; after the slurry control is completed, the ceramic core blank is dried, the ambient temperature is 23±5℃, the ambient humidity is 50±5%, the wind speed is 0.5-2m / s, and the drying time is 0.5-3h; after three surface modification treatments, the composite layer thickness of the ceramic core blank is 10-30μm.
[0025] In any of the above schemes, preferably, in step seven, after the third surface modification treatment is completed, the drying treatment parameters of the ceramic core blank are: ambient temperature 23±5°C, ambient humidity 50±5%, wind speed 0.5-2m / s, and drying time 0.5-3h.
[0026] In any of the above schemes, it is preferred that in step nine, the roasting process of the ceramic core blank is to place the calcination bowl containing kaolin filler and the ceramic core blank into a roasting furnace, and heat the temperature from room temperature to 180°C at a heating rate of 1-2°C / min, and keep it warm for 2-4h; continue to heat the temperature from 180°C to 900°C at a heating rate of 3-5°C / min, and keep it warm for 3-5h; continue to heat the temperature from 900°C to 1150-1350°C at a heating rate of 8-10°C / min, and keep it warm for 2-6h; continue to cool the temperature from 1150-1350°C to 800-1000°C at a cooling rate of 8-12°C / min, and then cool to room temperature with the furnace; after roasting, a surface-modified ceramic core is obtained, and the composite layer thickness of the surface-modified ceramic core is 5-25μm, the surface roughness is 1.5-3μm, and the high-temperature three-point bending strength is 8-20MPa.
[0027] In the present invention, the injection machine, vacuum pump, roasting furnace, etc. used are all traditional equipment, and there are no special requirements for the equipment structure and model. The manufacturing process of the ceramic core mold is a traditional process, and there are no special requirements for the process flow, process parameters, mold materials, manufacturing equipment, etc.; at the same time, the pressing process of the ceramic core blank is also a traditional process, and there are no special requirements for the process flow, process parameters, pressing equipment, etc., and it is only necessary to ensure that several key pressing parameters such as injection temperature, injection pressure, and holding time meet the requirements of the present invention. After roasting, the ceramic core is obtained, and the high-temperature three-point bending strength of the ceramic core must be controlled within a certain range. If the strength is too high, recrystallization is likely to occur. In addition, in the entire preparation process of the ceramic core, the material ratio and preparation process of the surface modified slurry, the three-time surface modification treatment process and process parameters of the ceramic core blank, and the roasting parameters of the ceramic core blank are all very important, and each parameter needs to work synergistically to achieve the expected technical effect of the present invention.
[0028] The surface-modified ceramic core prepared by the present invention has the following characteristics: (1) The composite part forms a protective layer to inhibit the volatilization of low-melting-point elements in the ceramic core and avoid the generation of excess metal nodules in the inner cavity of the blade during high-temperature casting; (2) The strength and stress of the ceramic core can be adjusted by surface modification to inhibit recrystallization in the inner cavity of the blade.
[0029] The ceramic core surface modification method for improving the inner cavity quality of a single-crystal hollow blade of the present invention has the following beneficial effects:
[0030] (1) After the ceramic core blank is pressed, the outer surface of the ceramic core blank is subjected to three surface modification treatments, and then the surface-modified ceramic core blank is fired to obtain a ceramic core. This method solves the problems of loose interface bonding and poor surface roughness in conventional coatings (the ceramic core blank is fired to obtain a ceramic core, and then a coating is applied to the outer surface of the ceramic core) and other modification treatments.
[0031] (2) The thickness of the composite layer on the outer surface of the ceramic core prepared by the present invention is controlled within a range of 5-25 μm, which will not affect the size and roughness of the inner cavity of the blade. The present invention can ensure the surface roughness of the ceramic core and the inner cavity size of the single crystal hollow blade casting while ensuring that the surface of the ceramic core is free of low-melting-point phases and has appropriate strength. It can also avoid or control the generation of excess metal and recrystallization in the inner cavity of the blade, thereby improving the quality of the inner cavity of the blade.
[0032] (3) The surface-modified ceramic core prepared by the present invention can effectively wrap the low-melting-point phase in the original ceramic core matrix after modification, inhibit the flow of the low-melting-point phase, reduce the volatilization and reaction of the low-melting-point phase at high temperature, and avoid the generation of excess metal nodules in the inner cavity of the blade after smelting and pouring.
[0033] (4) The surface-modified ceramic core prepared by the present invention can inhibit the crystallization of quartz on the surface of the ceramic core and adjust the bending strength of the ceramic core, so that the ceramic core can not only resist the mechanical impact and thermal shock of the molten metal without bending deformation and core leakage, but also ensure a certain degree of yielding to avoid recrystallization in the blade cavity. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 A flow chart of a preferred embodiment of a ceramic core surface modification method for improving the inner cavity quality of a single crystal hollow blade according to the present invention;
[0035] Figure 2 for Figure 1 A scanning electron microscope photograph of a cross section of a surface-modified ceramic core prepared in the illustrated embodiment;
[0036] Figure 3 To adopt Figure 1 X-ray photo of the inner cavity of a single-crystal hollow blade prepared by the surface-modified ceramic core of the embodiment shown (no recrystallization in the inner cavity of the blade);
[0037] Figure 4 To adopt Figure 1 X-ray photo of the inner cavity of a single-crystal hollow blade made of the surface-modified ceramic core of the embodiment shown (no excess metal in the inner cavity of the blade); Figure 5 for Figure 1 The illustrated embodiment shows a comparison of the ceramic core performance and the recrystallization of the hollow blade cavity before and after modification. DETAILED DESCRIPTION
[0038] In order to further understand the content of the present invention, the present invention will be described in detail below in conjunction with specific embodiments.
[0039] Embodiment 1:
[0040] like Figure 1 As shown, according to a preferred embodiment of the ceramic core surface modification method for improving the inner cavity quality of a single crystal hollow blade of the present invention, the modification method comprises the following steps in chronological order:
[0041] Step 1: manufacturing a ceramic core mold according to the designed ceramic core structure, and injecting the ceramic core slurry into the ceramic core mold by an injection molding machine for filling and pressing to obtain a ceramic core blank;
[0042] Step 2: Prepare surface modification slurry according to design requirements;
[0043] Step 3: Put the ceramic core blank into alcohol for cleaning, so that the surface of the ceramic core blank is clean and free of foreign matter; after the cleaning is completed, dry the ceramic core blank;
[0044] Step 4: After the drying process is completed, the ceramic core blank is placed in a vacuum device for vacuum treatment; after the vacuum treatment is completed, the ceramic core blank is completely immersed in the surface modification slurry for the first surface modification treatment;
[0045] Step 5: After the first surface modification treatment is completed, the ceramic core blank is directly immersed in the surface modification slurry for a second surface modification treatment without vacuum treatment;
[0046] Step 6: After the second surface modification treatment is completed, the ceramic core blank is directly immersed in the surface modification slurry for the third surface modification treatment without vacuum treatment;
[0047] Step 7: After the third surface modification treatment is completed, the ceramic core blank is placed in alcohol for cleaning and drying;
[0048] Step 8: Check the ceramic core blank and confirm that there are no obvious defects in its appearance, then insert the ceramic core blank into a calcined bowl filled with kaolin filler, and make the kaolin filler completely cover the ceramic core blank;
[0049] Step nine: placing the calcined pot containing the kaolin filler and the ceramic core blank into a calcining furnace for calcining. After the calcination is completed, a surface-modified ceramic core for improving the inner cavity quality of a single-crystal hollow blade is obtained.
[0050] In step one, the mass percentage of each substance in the ceramic core slurry is 78wt% of ceramic powder and 22wt% of plasticizer; the mass percentage of each substance in the ceramic powder is 80wt% of quartz glass powder, 12wt% of zirconium silicate powder, and 8wt% of mullite whisker, and the median particle size of the quartz glass powder and the zirconium silicate powder is 38μm; the mass percentage of each substance in the plasticizer is 82wt% of paraffin, 12wt% of beeswax, and 6wt% of polyethylene glycol.
[0051] The preparation process of the ceramic core slurry is as follows: first, quartz glass powder, zirconium silicate powder and mullite whisker are mixed uniformly at room temperature according to the designed material ratio to obtain ceramic powder; then, paraffin, beeswax and polyethylene glycol are placed in a container and heated to melt according to the designed material ratio, the heating temperature is 105° C., and the three substances are mixed uniformly to obtain a plasticizer; finally, the heating temperature is kept unchanged, the ceramic powder is added to the plasticizer and mixed uniformly to obtain the ceramic core slurry, and then the temperature is reduced to 90° C. and kept warm for standby use.
[0052] The pressing parameters of the ceramic core blank are injection temperature 90° C., injection pressure 5 MPa, and holding time 20 s.
[0053] In step 2, the mass percentage of each substance in the surface modified slurry is 58wt% of alumina powder, 38wt% of aluminum sol, 3.2wt% of silica sol, and 0.8wt% of dispersant; the median particle size of the alumina powder is 5μm, and the median particle sizes of the aluminum sol and the silica sol are both 18nm; the mass percentage of each substance in the dispersant is 40wt% of carboxymethyl cellulose emulsifier and 60wt% of polyoxyethylene.
[0054] The preparation process of the surface modified slurry is as follows: first, according to the designed material ratio, the carboxymethyl cellulose emulsifier and the polyethylene oxide are electromagnetically stirred at room temperature, the stirring speed is 80 rpm, the stirring time is 0.8 h, and the two substances are ensured to be evenly mixed to obtain a dispersant; then, according to the designed material ratio, the aluminum sol and the silica sol are electromagnetically stirred at room temperature, the stirring speed is 80 rpm, and the stirring time is 20 min, and the two substances are ensured to be evenly mixed; finally, alumina powder and a dispersant are added to the mixture of aluminum sol and silica sol, and electromagnetically stirred at room temperature, the stirring speed is 150 rpm, and the stirring time is 2 h, and the substances are ensured to be evenly mixed to obtain a surface modified slurry.
[0055] In step three, the drying parameters of the ceramic core blank are as follows: ambient temperature 23±5° C., ambient humidity 50±5%, wind speed 1.2 m / s, drying time 1.8 h, and the moisture content of the ceramic core blank after drying is below 2.5%.
[0056] In step four, the ceramic core blank is placed in a vacuum pumping device for vacuum treatment, and the vacuum degree is drawn to -0.06MPa; the first surface modification process of the ceramic core blank is to completely immerse the vacuumized ceramic core blank in the surface modification slurry for dipping, and the dipping time is 1.8h; after the dipping is completed, the ceramic core blank is taken out for slurry control, and the slurry control time is 12s; after the slurry control is completed, the ceramic core blank is dried, the ambient temperature is 23±5℃, the ambient humidity is 50±5%, the wind speed is 1.2m / s, and the drying time is 1.8h.
[0057] In step five, the second surface modification process of the ceramic core blank is to completely immerse the ceramic core blank after the first surface modification treatment in the surface modification slurry for dipping, and the dipping time is 0.8h; after the dipping is completed, the ceramic core blank is taken out for slurry control, and the slurry control time is 6s; after the slurry control is completed, the ceramic core blank is dried, the ambient temperature is 23±5℃, the ambient humidity is 50±5%, the wind speed is 1.2m / s, and the drying time is 1.8h.
[0058] In step six, the third surface modification process of the ceramic core blank is to completely immerse the ceramic core blank after the second surface modification treatment in the surface modification slurry for dipping, and the dipping time is 0.8h; after the dipping is completed, the ceramic core blank is taken out for slurry control, and the slurry control time is 4s; after the slurry control is completed, the ceramic core blank is dried, the ambient temperature is 23±5℃, the ambient humidity is 50±5%, the wind speed is 1.2m / s, and the drying time is 1.8h; after three surface modification treatments, the composite layer thickness of the ceramic core blank is 20μm.
[0059] In step seven, after the third surface modification treatment is completed, the drying treatment parameters of the ceramic core blank are: ambient temperature 23±5° C., ambient humidity 50±5%, wind speed 1.2 m / s, and drying time 1.8 h.
[0060] In step nine, the roasting process of the ceramic core blank is as follows: put the calcined bowl containing kaolin filler and the ceramic core blank into a roasting furnace, heat the temperature from room temperature to 180°C at a heating rate of 1.5°C / min, and keep it warm for 3 hours; continue to heat the temperature from 180°C to 900°C at a heating rate of 4°C / min, and keep it warm for 4 hours; continue to heat the temperature from 900°C to 1250°C at a heating rate of 9°C / min, and keep it warm for 4 hours; continue to cool the temperature from 1250°C to 900°C at a cooling rate of 10°C / min, and then cool to room temperature with the furnace; after roasting, a surface-modified ceramic core is obtained, and the composite layer thickness of the surface-modified ceramic core is 15μm, the surface roughness is 2.2μm, and the high-temperature three-point bending strength is 15.5MPa.
[0061] The scanning electron microscope photograph of the cross section of the surface modified ceramic core prepared in this embodiment is as follows: Figure 2 As shown in the figure, it can be seen that the particle size of the surface modified slurry is small, the distribution is uniform, and the bonding with the ceramic core matrix is strong. The surface modified ceramic core prepared in this embodiment is further used to prepare a single crystal hollow blade. The X-ray photo of the inner cavity of the blade is shown in FIG. Figure 3 and Figure 4 As shown, from Figure 3 It can be seen that there is no recrystallization in the blade cavity. Figure 4 It can be seen that there is no excess metal inside the blade cavity.
[0062] After the ceramic core blank is obtained in this embodiment, it is subjected to three surface modification treatments and then fired to obtain a ceramic core. The ceramic core is a surface-modified ceramic core. If the ceramic core blank is not subjected to surface modification treatment after it is obtained, but is directly fired to obtain a ceramic core, the same ceramic core slurry, pressing process and pressing parameters, firing process and firing parameters as in this embodiment are used in the preparation process. The performance of the ceramic core before and after modification and the recrystallization of the inner cavity of the hollow blade are compared, and the comparison results are shown as follows. Figure 5 As shown in the figure, it can be seen that the high-temperature three-point bending strength of the modified ceramic core is about 15.5MPa, and the recrystallization ratio of the blade cavity is basically 0%, that is, the hollow blades produced in the same batch have no recrystallization, while the high-temperature three-point bending strength of the unmodified ceramic core reaches 22MPa. Excessive strength will cause recrystallization, and the recrystallization ratio of the blade cavity reaches 18%.
[0063] In this embodiment, the injection machine, vacuum pump, roasting furnace, etc. used are all traditional equipment, and there are no special requirements for the equipment structure and model. The manufacturing process of the ceramic core mold is a traditional process, and there are no special requirements for the process flow, process parameters, mold materials, manufacturing equipment, etc.; At the same time, the pressing process of the ceramic core blank is also a traditional process, and there are no special requirements for the process flow, process parameters, pressing equipment, etc., and it is only necessary to ensure that the injection temperature, injection pressure, holding time and other key pressing parameters meet the requirements of the present invention. After roasting, the ceramic core is obtained, and the high-temperature three-point bending strength of the ceramic core must be controlled within the range of 8-20MPa. If the strength is too high, recrystallization is likely to occur. In addition, in the entire preparation process of the ceramic core, the material ratio and preparation process of the surface modified slurry, the three-time surface modification treatment process and process parameters of the ceramic core blank, and the roasting parameters of the ceramic core blank are all very important, and each parameter needs to work together to achieve the technical effect expected by this embodiment.
[0064] The ceramic core surface modification method for improving the inner cavity quality of a single-crystal hollow blade in this embodiment has the following beneficial effects:
[0065] (1) The problem of loose interface bonding and poor surface roughness during conventional coating and other modification treatments is solved. (2) While ensuring the surface roughness of the ceramic core and the inner cavity size of the single crystal hollow blade casting, the surface of the ceramic core can be free of low-melting point phases and have appropriate strength. It can also avoid or control the generation of excess metal and recrystallization in the blade cavity, thereby improving the quality of the blade cavity. (3) The modified composite structure can effectively wrap the low-melting point phase in the original ceramic core matrix, inhibit the flow of the low-melting point phase, reduce the volatilization and reaction of the low-melting point phase at high temperature, and avoid the generation of excess metal nodules in the blade cavity after smelting and pouring. (4) It can inhibit the crystallization of quartz on the surface of the ceramic core and adjust the bending strength of the ceramic core, so that the ceramic core can resist the mechanical impact and thermal shock of the molten metal without bending deformation and core leakage, and can also ensure a certain degree of concession to avoid recrystallization in the blade cavity.
[0066] Embodiment 2:
[0067] According to another preferred embodiment of the ceramic core surface modification method for improving the inner cavity quality of a single crystal hollow blade of the present invention, its process flow, technical principle, beneficial effects, etc. are basically the same as those of the first embodiment, except that:
[0068] In step one, the mass percentage of each substance in the ceramic core slurry is 70wt% of ceramic powder and 30wt% of plasticizer; the mass percentage of each substance in the ceramic powder is 70wt% of quartz glass powder, 20wt% of zirconium silicate powder, and 10wt% of mullite whisker, and the median particle size of the quartz glass powder and the zirconium silicate powder are both 25μm; the mass percentage of each substance in the plasticizer is 80wt% of paraffin, 15wt% of beeswax, and 5wt% of polyethylene glycol.
[0069] The preparation process of the ceramic core slurry is as follows: first, quartz glass powder, zirconium silicate powder, and mullite whisker are mixed uniformly at room temperature according to the designed material ratio to obtain ceramic powder; then, paraffin, beeswax, and polyethylene glycol are placed in a container and heated to melt according to the designed material ratio, and the heating temperature is 90°C, and the three substances are mixed uniformly to obtain a plasticizer; finally, the heating temperature is kept unchanged, and the ceramic powder is added to the plasticizer and mixed uniformly to obtain a ceramic core slurry, and then the temperature is reduced to 80°C and kept warm for use. The pressing parameters of the ceramic core blank are injection temperature 80°C, injection pressure 4MPa, and holding time 35s.
[0070] In step 2, the mass percentage of each substance in the surface modified slurry is 50wt% of alumina powder, 45wt% of aluminum sol, 4.5wt% of silica sol, and 0.5wt% of dispersant; the median particle size of the alumina powder is 1μm, and the median particle sizes of the aluminum sol and the silica sol are both 5nm; the mass percentage of each substance in the dispersant is 30wt% of carboxymethyl cellulose emulsifier and 70wt% of polyoxyethylene.
[0071] The preparation process of the surface modified slurry is as follows: first, according to the designed material ratio, the carboxymethyl cellulose emulsifier and the polyethylene oxide are electromagnetically stirred at room temperature, the stirring speed is 50 rpm, the stirring time is 1 hour, and the two substances are ensured to be evenly mixed to obtain a dispersant; then, according to the designed material ratio, the aluminum sol and the silica sol are electromagnetically stirred at room temperature, the stirring speed is 50 rpm, and the stirring time is 30 minutes, and the two substances are ensured to be evenly mixed; finally, alumina powder and a dispersant are added to the mixture of aluminum sol and silica sol, and electromagnetically stirred at room temperature, the stirring speed is 100 rpm, and the stirring time is 3 hours, and the substances are ensured to be evenly mixed to obtain a surface modified slurry.
[0072] In step three, the drying parameters of the ceramic core blank are as follows: ambient temperature 23±5° C., ambient humidity 50±5%, wind speed 0.5 m / s, drying time 3 h, and the moisture content of the ceramic core blank after drying is below 2.5%.
[0073] In step four, the ceramic core blank is placed in a vacuum pumping device for vacuum treatment, and the vacuum degree is drawn to -0.05MPa; the first surface modification process of the ceramic core blank is to completely immerse the vacuumized ceramic core blank in the surface modification slurry for dipping, and the dipping time is 0.5h; after the dipping is completed, the ceramic core blank is taken out for slurry control, and the slurry control time is 10s; after the slurry control is completed, the ceramic core blank is dried, the ambient temperature is 23±5℃, the ambient humidity is 50±5%, the wind speed is 0.5m / s, and the drying time is 3h.
[0074] In step five, the second surface modification process of the ceramic core blank is to completely immerse the ceramic core blank after the first surface modification treatment in the surface modification slurry for dipping, and the dipping time is 0.5h; after the dipping is completed, the ceramic core blank is taken out for slurry control, and the slurry control time is 5s; after the slurry control is completed, the ceramic core blank is dried, the ambient temperature is 23±5℃, the ambient humidity is 50±5%, the wind speed is 0.5m / s, and the drying time is 3h.
[0075] In step six, the third surface modification process of the ceramic core blank is to completely immerse the ceramic core blank after the second surface modification treatment in the surface modification slurry for dipping, and the dipping time is 0.5h; after the dipping is completed, the ceramic core blank is taken out for slurry control, and the slurry control time is 3s; after the slurry control is completed, the ceramic core blank is dried, the ambient temperature is 23±5℃, the ambient humidity is 50±5%, the wind speed is 0.5m / s, and the drying time is 3h; after three surface modification treatments, the composite layer thickness of the ceramic core blank is 10μm.
[0076] In step seven, after the third surface modification treatment is completed, the drying treatment parameters of the ceramic core blank are: ambient temperature 23±5° C., ambient humidity 50±5%, wind speed 0.5 m / s, and drying time 3 h.
[0077] In step nine, the roasting process of the ceramic core blank is as follows: placing the calcining bowl containing the kaolin filler and the ceramic core blank into a roasting furnace, heating the temperature from room temperature to 180°C at a heating rate of 1°C / min, and keeping it warm for 4 hours; continuing to heat the temperature from 180°C to 900°C at a heating rate of 3°C / min, and keeping it warm for 5 hours; continuing to heat the temperature from 900°C to 1150°C at a heating rate of 8°C / min, and keeping it warm for 6 hours; continuing to cool the temperature from 1150°C to 800°C at a cooling rate of 8°C / min, and then cooling to room temperature with the furnace; after roasting, a surface-modified ceramic core is obtained, and the composite layer thickness of the surface-modified ceramic core is 5μm, the surface roughness is 1.5μm, and the high-temperature three-point bending strength is 10.2MPa.
[0078] Embodiment three:
[0079] According to another preferred embodiment of the ceramic core surface modification method for improving the inner cavity quality of a single crystal hollow blade of the present invention, its process flow, technical principle, beneficial effects, etc. are basically the same as those of the first embodiment, except that:
[0080] In step one, the mass percentage of each substance in the ceramic core slurry is 85wt% of ceramic powder and 15wt% of plasticizer; the mass percentage of each substance in the ceramic powder is 90wt% of quartz glass powder, 5wt% of zirconium silicate powder, and 5wt% of mullite whisker, and the median particle size of the quartz glass powder and the zirconium silicate powder is 50μm; the mass percentage of each substance in the plasticizer is 82wt% of paraffin, 10wt% of beeswax, and 8wt% of polyethylene glycol.
[0081] The preparation process of the ceramic core slurry is as follows: first, quartz glass powder, zirconium silicate powder, and mullite whisker are mixed uniformly at room temperature according to the designed material ratio to obtain ceramic powder; then, paraffin, beeswax, and polyethylene glycol are placed in a container and heated to melt according to the designed material ratio, the heating temperature is 120°C, and the three substances are mixed uniformly to obtain a plasticizer; finally, the heating temperature is kept unchanged, the ceramic powder is added to the plasticizer and mixed uniformly to obtain a ceramic core slurry, and then the temperature is reduced to 100°C and kept warm for standby use. The pressing parameters of the ceramic core blank are injection temperature 100°C, injection pressure 6MPa, and holding time 5s.
[0082] In step 2, the mass percentage of each substance in the surface modified slurry is 65wt% of alumina powder, 30wt% of aluminum sol, 4wt% of silica sol, and 1wt% of dispersant; the median particle size of the alumina powder is 10μm, and the median particle sizes of the aluminum sol and the silica sol are both 30nm; the mass percentage of each substance in the dispersant is 50wt% of carboxymethyl cellulose emulsifier and 50wt% of polyoxyethylene.
[0083] The preparation process of the surface modified slurry is as follows: first, according to the designed material ratio, the carboxymethyl cellulose emulsifier and the polyethylene oxide are electromagnetically stirred at room temperature, the stirring speed is 100 rpm, the stirring time is 0.5 h, and the two substances are ensured to be evenly mixed to obtain a dispersant; then, according to the designed material ratio, the aluminum sol and the silica sol are electromagnetically stirred at room temperature, the stirring speed is 100 rpm, and the stirring time is 10 min, and the two substances are ensured to be evenly mixed; finally, alumina powder and a dispersant are added to the mixture of aluminum sol and silica sol, and electromagnetically stirred at room temperature, the stirring speed is 200 rpm, and the stirring time is 1 h, and the substances are ensured to be evenly mixed to obtain a surface modified slurry.
[0084] In step three, the drying parameters of the ceramic core blank are as follows: ambient temperature 23±5° C., ambient humidity 50±5%, wind speed 2 m / s, drying time 0.5 h. After drying, the water content of the ceramic core blank is below 2.5%.
[0085] In step four, the ceramic core blank is placed in a vacuum pumping device for vacuum treatment, and the vacuum degree is drawn to -0.08MPa; the first surface modification process of the ceramic core blank is to completely immerse the vacuumized ceramic core blank in the surface modification slurry for dipping, and the dipping time is 3h; after the dipping is completed, the ceramic core blank is taken out for slurry control, and the slurry control time is 15s; after the slurry control is completed, the ceramic core blank is dried, the ambient temperature is 23±5℃, the ambient humidity is 50±5%, the wind speed is 2m / s, and the drying time is 0.5h.
[0086] In step five, the second surface modification process of the ceramic core blank is to completely immerse the ceramic core blank after the first surface modification treatment in the surface modification slurry for dipping, and the dipping time is 1 hour; after the dipping is completed, the ceramic core blank is taken out for slurry control, and the slurry control time is 8 seconds; after the slurry control is completed, the ceramic core blank is dried, the ambient temperature is 23±5°C, the ambient humidity is 50±5%, the wind speed is 2m / s, and the drying time is 0.5h.
[0087] In step six, the third surface modification process of the ceramic core blank is to completely immerse the ceramic core blank after the second surface modification treatment in the surface modification slurry for dipping for 1 hour; after the dipping is completed, the ceramic core blank is taken out for slurry control for 5 seconds; after the slurry control is completed, the ceramic core blank is dried, the ambient temperature is 23±5°C, the ambient humidity is 50±5%, the wind speed is 2m / s, and the drying time is 0.5h; after three surface modification treatments, the composite layer thickness of the ceramic core blank is 30μm.
[0088] In step seven, after the third surface modification treatment is completed, the drying treatment parameters of the ceramic core blank are: ambient temperature 23±5° C., ambient humidity 50±5%, wind speed 2 m / s, and drying time 0.5 h.
[0089] In step nine, the roasting process of the ceramic core blank is as follows: placing the calcining bowl containing kaolin filler and the ceramic core blank into a roasting furnace, heating the temperature from room temperature to 180°C at a heating rate of 2°C / min, and keeping it warm for 2 hours; continuing to heat the temperature from 180°C to 900°C at a heating rate of 5°C / min, and keeping it warm for 3 hours; continuing to heat the temperature from 900°C to 1350°C at a heating rate of 10°C / min, and keeping it warm for 2 hours; continuing to cool the temperature from 1350°C to 1000°C at a cooling rate of 12°C / min, and then cooling to room temperature with the furnace; after roasting, a surface-modified ceramic core is obtained, and the composite layer thickness of the surface-modified ceramic core is 25μm, the surface roughness is 3μm, and the high-temperature three-point bending strength is 18.7MPa.
[0090] Special note: The technical solution of the present invention involves many parameters, and the synergistic effects between the various parameters need to be comprehensively considered to obtain the beneficial effects and significant progress of the present invention. Moreover, the value ranges of the various parameters in the technical solution are obtained after a large number of experiments. For each parameter and the combination of each parameter, the inventor has recorded a large amount of experimental data. Due to space limitations, the specific experimental data will not be disclosed here.
[0091] It is not difficult for those skilled in the art to understand that the surface modification method of the ceramic core for improving the inner cavity quality of the single crystal hollow blade of the present invention includes any combination of the invention content and the specific implementation method of the above-mentioned invention specification and the various parts shown in the drawings. Due to the limited space and to make the specification concise, the various schemes composed of these combinations are not described one by one. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A ceramic core surface modification method for improving the inner cavity quality of a single crystal hollow blade, characterized in that: The modification method comprises the following steps in chronological order: Step 1: manufacturing a ceramic core mold according to the designed ceramic core structure, and injecting the ceramic core slurry into the ceramic core mold by an injection molding machine for filling and pressing to obtain a ceramic core blank; Step 2: Prepare surface modification slurry according to design requirements; Step 3: Put the ceramic core blank into alcohol for cleaning, so that the surface of the ceramic core blank is clean and free of foreign matter; after the cleaning is completed, dry the ceramic core blank; Step 4: After the drying process is completed, the ceramic core blank is placed in a vacuum device for vacuum treatment; after the vacuum treatment is completed, the ceramic core blank is completely immersed in the surface modification slurry for the first surface modification treatment; Step 5: After the first surface modification treatment is completed, the ceramic core blank is directly immersed in the surface modification slurry for a second surface modification treatment without vacuum treatment; Step 6: After the second surface modification treatment is completed, the ceramic core blank is directly immersed in the surface modification slurry for the third surface modification treatment without vacuum treatment; Step 7: After the third surface modification treatment is completed, the ceramic core blank is placed in alcohol for cleaning and drying; Step 8: Check the ceramic core blank and confirm that there are no obvious defects in its appearance, then insert the ceramic core blank into a calcined bowl filled with kaolin filler, and make the kaolin filler completely cover the ceramic core blank; Step nine: placing the calcined pot containing the kaolin filler and the ceramic core blank into a calcining furnace for calcining, and after the calcination is completed, a surface-modified ceramic core for improving the inner cavity quality of the single crystal hollow blade is obtained; In step 1, the mass percentage of each substance in the ceramic core slurry is 70-85wt% of ceramic powder and 15-30wt% of plasticizer; the mass percentage of each substance in the ceramic powder is 70-90wt% of quartz glass powder, 5-20wt% of zirconium silicate powder, and 5-10wt% of mullite whisker, and the median particle size of the quartz glass powder and the zirconium silicate powder is 25-50μm; the mass percentage of each substance in the plasticizer is 80-85wt% of paraffin, 10-15wt% of beeswax, and 5-8wt% of polyethylene glycol; In step 2, the mass percentage of each substance in the surface modified slurry is 50-65wt% of alumina powder, 30-45wt% of aluminum sol, 1-5wt% of silica sol, and 0.5-1wt% of dispersant; the median particle size of the alumina powder is 1-10μm, and the median particle sizes of the aluminum sol and the silica sol are both 5-30nm; the mass percentage of each substance in the dispersant is 30-50wt% of carboxymethyl cellulose emulsifier and 50-70wt% of polyoxyethylene.
2. The method for surface modification of a ceramic core for improving the inner cavity quality of a single crystal hollow blade according to claim 1, characterized in that: In step one, the preparation process of the ceramic core slurry is as follows: first, according to the designed material ratio, quartz glass powder, zirconium silicate powder, and mullite whisker are mixed uniformly at room temperature to obtain ceramic powder; then, according to the designed material ratio, paraffin, beeswax, and polyethylene glycol are placed in a container and heated to melt, the heating temperature is 90-120°C, and the three substances are mixed uniformly to obtain a plasticizer; finally, the heating temperature is kept unchanged, the ceramic powder is added to the plasticizer and mixed uniformly to obtain a ceramic core slurry, and then the temperature is reduced to 80-100°C, and the heat is kept for standby use; the pressing parameters of the ceramic core blank are injection temperature 80-100°C, injection pressure 4-6MPa, and holding time 5-35s.
3. The ceramic core surface modification method for improving the inner cavity quality of a single crystal hollow blade according to claim 2, characterized in that: In step 2, the preparation process of the surface modified slurry is as follows: first, according to the designed material ratio, the carboxymethyl cellulose emulsifier and the polyethylene oxide are electromagnetically stirred at room temperature, the stirring speed is 50-100rpm, and the stirring time is 0.5-1h, to ensure that the two substances are evenly mixed to obtain a dispersant; then, according to the designed material ratio, the aluminum sol and the silica sol are electromagnetically stirred at room temperature, the stirring speed is 50-100rpm, and the stirring time is 10-30min, to ensure that the two substances are evenly mixed; finally, alumina powder and dispersant are added to the mixture of aluminum sol and silica sol, and electromagnetically stirred at room temperature, the stirring speed is 100-200rpm, and the stirring time is 1-3h, to ensure that the substances are evenly mixed to obtain a surface modified slurry.
4. The method for surface modification of a ceramic core for improving the inner cavity quality of a single crystal hollow blade according to claim 3, characterized in that: In step three, the drying parameters of the ceramic core blank are as follows: ambient temperature 23±5°C, ambient humidity 50±5%, wind speed 0.5-2m / s, drying time 0.5-3h, and the moisture content of the ceramic core blank after drying is below 2.5%.
5. The method for surface modification of a ceramic core for improving the inner cavity quality of a single crystal hollow blade according to claim 4, characterized in that: In step four, the ceramic core blank is placed in a vacuum pumping device for vacuum treatment, and the vacuum degree is drawn to -0.05~-0.08MPa; the first surface modification process of the ceramic core blank is to completely immerse the vacuumized ceramic core blank in the surface modification slurry for dipping, and the dipping time is 0.5-3h; after the dipping is completed, the ceramic core blank is taken out for slurry control, and the slurry control time is 10-15s; after the slurry control is completed, the ceramic core blank is dried, the ambient temperature is 23±5℃, the ambient humidity is 50±5%, the wind speed is 0.5-2m / s, and the drying time is 0.5-3h.
6. The method for surface modification of a ceramic core for improving the inner cavity quality of a single crystal hollow blade according to claim 5, characterized in that: In step five, the second surface modification process of the ceramic core blank is to completely immerse the ceramic core blank after the first surface modification treatment in the surface modification slurry for dipping, and the dipping time is 0.5-1h; after the dipping is completed, the ceramic core blank is taken out for slurry control, and the slurry control time is 5-8s; after the slurry control is completed, the ceramic core blank is dried, the ambient temperature is 23±5℃, the ambient humidity is 50±5%, the wind speed is 0.5-2m / s, and the drying time is 0.5-3h.
7. The ceramic core surface modification method for improving the inner cavity quality of a single crystal hollow blade according to claim 6, characterized in that: In step six, the third surface modification process of the ceramic core blank is to completely immerse the ceramic core blank after the second surface modification treatment in the surface modification slurry for dipping, and the dipping time is 0.5-1h; after the dipping is completed, the ceramic core blank is taken out for slurry control, and the slurry control time is 3-5s; after the slurry control is completed, the ceramic core blank is dried, the ambient temperature is 23±5℃, the ambient humidity is 50±5%, the wind speed is 0.5-2m / s, and the drying time is 0.5-3h; after three surface modification treatments, the composite layer thickness of the ceramic core blank is 10-30μm.
8. The ceramic core surface modification method for improving the inner cavity quality of a single crystal hollow blade according to claim 7, characterized in that: In step seven, after the third surface modification treatment is completed, the drying treatment parameters of the ceramic core blank are: ambient temperature 23±5° C., ambient humidity 50±5%, wind speed 0.5-2 m / s, and drying time 0.5-3 h.
9. The ceramic core surface modification method for improving the inner cavity quality of a single crystal hollow blade according to claim 8, characterized in that: In step nine, the roasting process of the ceramic core blank is as follows: placing the calcined bowl containing the kaolin filler and the ceramic core blank into a roasting furnace, heating the temperature from room temperature to 180°C at a heating rate of 1-2°C / min, and keeping it warm for 2-4h; continuing to heat the temperature from 180°C to 900°C at a heating rate of 3-5°C / min, and keeping it warm for 3-5h; continuing to heat the temperature from 900°C to 1150-1350°C at a heating rate of 8-10°C / min, and keeping it warm for 2-6h; continuing to cool the temperature from 1150-1350°C to 800-1000°C at a cooling rate of 8-12°C / min, and then cooling to room temperature with the furnace; after roasting, a surface-modified ceramic core is obtained, and the composite layer thickness of the surface-modified ceramic core is 5-25μm, the surface roughness is 1.5-3μm, and the high-temperature three-point bending strength is 8-20MPa.
